Convergence and Extended Linear Generating Function for Generalized Hypergeometric Function (International journal of recent technology and engineering, 2019)
The subject of Special functions has a lot importance during the last few decades. The intend of this work is to test the convergence and to introduce the extended linear generating relation for the generalized hypergeometric function. The result is followed by its applications to the classical polynomials.